Development of air conditioner split R32 trainer learning media in cooling and air conditioning engineering courses - Fitria Wahyu Ningsih; Ilham Akbar Darmawan; Mohammad Fatkhurrokhman (Jurnal Pendidikan Vokasi, 2021)
This study aims to develop learning media for AC Split R32 in the subject of refrigeration and air conditioning engineering. The method used Research and Development (R&D), the model of research used is Successive Approximation Models 1 (SAM). The model goes through iteration 1 (Evaluate 1, Design 1, Develop 1), iteration 2 (Evaluate 2, Design 2, Develop 2), and iteration 3 (Evaluate 3, and product implementation). The data collection method uses instruments in the form of observations, interviews, literature studies, and questionnaires that use a Likert scale for measurement the instrument. Based on the research analysis results, media trainers get an average of 76 in the "Very Eligible" category. Then the material results get an average of 63.5 which states that job sheets are in the "Very Eligible" category. Meanwhile, for the feasibility test on 30 student respondents, an average of 71.8 was obtained in the "Very Eligible" category. Meanwhile, based on the performance practice assessment, the average result was 83.4 out of 10 students who practiced in the "Good" assessment category. Thus, based on the development research, the trainer and job sheet can be used as learning media.